Nanorobots with Hybrid Biomembranes for Simultaneous Degradation of Toxic Microorganism. (23rd September 2022) - Refaai, Mohamad Reda A.; Manjunatha, M. N.; Radjarejesri, S.; Ramesh, B.; Subbiah, Ram; Adugna, Nahom
Abstract : Nanorobotics is a modern technological sector that creates robots with elements that are close to or near the nanoscale scale of such a nanometer. To be more specific, nanorobotics has been the nanotechnology approach to designing and creating nanorobots. Also, with the fast growth of robotics technology, developing biomaterials micro- or nanorobots, which convert biological concepts into a robotic device, grows progressively vital. This proposes the development, manufacturing, and testing of a dual–cell membrane–functionalized nanorobot for multifunctional biological threat component elimination, with a focus on the simultaneous targeted and neutralization of the pathogenic bacteria and toxins. Ultrasound-propelled biomaterials nanorobots comprised of the gold nanostructures wrapped in a combination of platelet (PL) and Red Blood Cell (RBC) layers were developed. Biohybrid micro- and nanorobots were small machines that combine biological and artificial elements. They may benefit from onboard actuators, detection, management, and deployment of a variety in medical functions. These hybrid cell walls consist of a variety of structural proteins involved in living organism RBCs and PLs, which provide nanorobots with either a quantity of the appealing biological functionality, with bonding and adhesion to the PL-adhering pathogenic organisms (for example, staphylococcus bacteria) but also neutralization of the pore-forming toxins (e.g., toxin). Furthermore, the biomaterials nanorobots demonstrated quick and efficient extended sonic propulsion for total blood with really no visible bacterial growth and mirrored the movements of genuine cell separation. This propulsion improved the robots' bonding and detoxifying efficacy against infections and poisons. Overall, combining this diversified physiological activity of hybrid cellular tissue with the energy propulsion of such robotic systems contributed to the dynamic robotics scheme for effective separation and synchronous elimination of various living risks, a significant step towards to development of a broad-spectrum detoxifying robotic framework.